Detection of a genetically related carbapenemase-producing Escherichia coli ST167 in clinical and environmental isolates: Evidence for clonal spread of carbapenemase-producing Enterobacteriaceae in humans and the environment in Iowa, United States - Hanseob Shin; David M. Cwiertny; Megan J. Nelson; Ryan T. Jepson; Michael A. Pentella; Darrin A. Thompson (Journal of Global Antimicrobial Resistance)
Background: Carbapenemase-producing Enterobacteriaceae (CPE) are listed by the World Health Organization as one of the critical priority pathogens needing urgent attention to address global resistance to antimicrobials. Thus, the transmission and epidemiology of CPEs need to be studied via One Health perspectives. Methods: An environmental CPE, referred to as BO1, was isolated from a creek in Northwest Iowa using a Colilert system (IDEXX, Westbrook, ME, USA). The presence of carbapenemase was examined using the modified carbapenem inactivation test, and then phenotypic resistance was determined using a Sensititre Complete Automated AST System (Thermo Fisher Scientific, Roskilde, Denmark). Whole-genome sequencing was performed and analysed to compare with clinical CPEs. Results: BO1, carrying blaNDM-5, was isolated from a creek in Northwest Iowa. BO1 exhibited resistance to 15 antimicrobials and was defined as an extensively drug-resistant organism. BO1 was also identified as ST167, which is well known as an emerging high-risk clone, and IncFIA- and IncQ1-type conjugatable plasmids were identified within the BO1 genome. The genetic environment of blaNDM-5 was highly conserved as blaNDM-bleMBL-trpF-dsbD in all strains studied. Interestingly, single-nucleotide polymorphism analysis revealed that BO1 shared only 1, 4 and 12 single-nucleotide polymorphisms with three different clinical strains from patients at Iowa health care facilities. Conclusions: The occurrence of BO1 was temporally and spatially close to that of one clinical strain, IA0018, implying the clonal spread of CPEs among humans and the environment, although the source and directionality of this spread remains unknown. This report illustrates the need for the strict control of CPEs in health care facilities and continuous surveillance within clinical and environmental settings to trace and prevent CPE transmission.